Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1063/1.4978646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of optical material properties on strong coupling in organic semiconductor based microcavities

Abstract: The optical properties of organic semiconductors are generally characterised by a number of material specific parameters, including absorbance, photoluminescence quantum yield, Stokes shift, and molecular orientation. Here, we study four different organic semiconductors and compare their optical properties to the characteristics of the exciton-polaritons that are formed when these materials are introduced into metal-clad microcavities. We find that the strength of coupling between cavity photons and excitons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
(44 reference statements)
2
34
0
1
Order By: Relevance
“…(A similar experimental result was reported, without explanation, in ref. .) Their spectral positions follow two low‐wavelength branches of the calculated dispersion curve, Figure d, triangles.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…(A similar experimental result was reported, without explanation, in ref. .) Their spectral positions follow two low‐wavelength branches of the calculated dispersion curve, Figure d, triangles.…”
Section: Resultsmentioning
confidence: 81%
“…On the other hand, if the coupling energy exceeds relaxation and dephasing rates of interacting oscillators (e.g., excitons and resonant cavities), the strong coupling regime, manifested by the Rabi splitting of hybrid excited states and the corresponding avoided crossing behavior of the dispersion curves, is taking place. In this case, the energy eigenvalues can alter dramatically (≈1 eV), leading to a change of the surface potential, electric conductivity, and (much stronger than in a weak coupling regime) change of the energy transfer and pathways of chemical reactions . The strong coupling is, reportedly, enabled by vacuum fluctuations and does not require photons .…”
Section: Introductionmentioning
confidence: 98%
“…The nonradiative decay mechanism in DPPT‐BT might be enhanced by further negative detuning, as more vibrational modes of the thiophene, DPP, and BT units are located at just slightly higher energies of 169–187 meV (1366–1510 cm −1 ) . So far there are only a handful examples of polymers showing strong coupling, and further investigation into the particular LP population mechanisms of these materials is highly desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Especially polariton condensation and polariton lasing have not yet been observed. Other polymers with more inhomogeneous broadening (including PFO, see Figure 6c) also show strong coupling [370] and even electrically pumped exciton-polaritons in cavity-integrated FETs. Plumhof et al could demonstrated polariton condensation at room temperature with a MeLPPP film in a high quality DBR microcavity.…”
Section: Exciton-polaritons In Microcavitiesmentioning
confidence: 99%
“…The nonlinearity is caused by stimulated scattering into the polariton ground state, which was further corroborated by long‐range phase coherence. Other polymers with more inhomogeneous broadening (including PFO, see Figure c) also show strong coupling and even electrically pumped exciton–polaritons in cavity‐integrated FETs …”
Section: Applicationsmentioning
confidence: 99%